High Drying Temperature Accelerates Sunflower Seed Deterioration by Regulating the Fatty Acid Metabolism, Glycometabolism, and Abscisic Acid/Gibberellin Balance - Huang, Yutao; Lu, Min; Wu, Huaping; Zhao, Tiyuan; Wu, Pin; Cao, Dongdong (Frontiers in Plant Science, 2021)
Sunflower seed storage is accompanied by the loss of seed vigor. Seed drying is a key link between seed harvest and seed storage; however, to date, the effect of seed drying on sunflower seed deterioration during storage remains unclear. The present study performed hot air drying for sunflower seeds with an initial moisture content of 30% to examine the manner in which drying temperature (35°C, 40°C, 45°C, 50°C, and 55°C) affects the drying performance and seed vigor following storage process (6 and 12 months). A drying temperature of 40ºC was evidently safe for sunflower seeds, whereas the high drying temperatures (HTD, 45°C, 50°C, and 55°C) significantly lowered sunflower seed vigor by regulating the fatty acid metabolism, glycometabolism, and abscisic acid (ABA)/gibberellin (GA) balance. HDT significantly increased the seed damage rate and accelerated sunflower seed deterioration during natural and artificial aging process. Further biochemical analysis indicated that HDT significantly increased lipoxygenase and dioxygenase activities, leading to malonaldehyde and reactive oxygen species over-accumulation during storage. During early seed germination, HDT significantly inhibited fatty acid hydrolysis and glycometabolism by decreasing triacylglycerol lipase, CoA-SH oxidase, and invertase activities. Moreover, HDT remarkably increased ABA levels but reduced GA levels by regulating gene expressions and metabolic enzyme activities during early imbibitions. Cumulatively, the seed drying effect on sunflower seed vigor deterioration during the storage process may be strongly related to fatty acid oxidation and hydrolysis metabolism, toxic substance accumulation, and ABA/GA balance.